Giant mucocele of the appendix – laparoscopic management: A case report and review of the literature (Indian Journal of Case Reports, 2020)
A mucocele is an uncommon lesion of the appendix characterized by cystic distension of the appendicular lumen due to the accumulation of a mucoid substance known as mucin. It is often asymptomatic and surgical treatment depends on the histology and the dimension of the mucocele. We, herein, report a laparoscopically managed case of a 55-year-old male who presented with a large mobile mass in the lower abdomen. Abdominal contrast-enhanced computed tomography revealed a large mucocele of the appendix.